Towards Fluorinated Substrate Analogs and N-Acylated 2-Aminopyrimidine Inhibitors of Lipoxygenases - Haycock, Meghan Lynn (Université d'Ottawa / University of Ottawa, 2014)
Cyclooxygenase (COX) and lipoxygenase (LOX) catalyze the rate-determining step in the production of arachidonic acid- derived signaling molecules (eicosanoids) within the body. COX has been extensively investigated, which has enabled the design of non-steroidal inflammatory drugs (NSAIDs) such as aspirin, acetaminophen (ApAP) and ibuprofen. However, there are still fundamental questions surrounding the LOX family of enzymes, which has limited the development of isoform specific inhibitors. The structural basis and regio- and stereoselectivity of the LOX isoforms are not known. Herein, we describe two strategies to develop isoform-specific inhibitors of lipoxygenase. Efforts were focused on the synthesis of unnatural lipid derivatives, in which the methylene hydrogen atoms on the substrate were replaced with a moiety lacking a labile hydrogen atom, such as fluorine. This would allow the LOX enzyme to remain in an active form, while preventing enzyme turnover. This preliminary work will enable the assessment of their activity as inhibitors and attempts at their co-crystallization might provide the first insight into the binding mode of these fatty acid substrates. The preparation of a small library of acylated 2-aminopyrimidines and their efficacy as inhibitors of soybean lipoxygenase-1 was explored. Preliminary studies suggest the mode of action occurs through a bi-dentate coordination of the ferric iron atom. Modifications of the acylated 2-aminopyrimidines to make it more substrate-like and to increase its lipophilicity, yielded inhibitors with low micromolar IC50 values. With further optimization, acyl 2-aminopyrimidines could serve as a useful platform for the discovery of safe and efficient isoform specific inhibitors.
Keywords: Lipoxygenase; Fluorinated Substrate Analogs